Analisis Kinerja Mesin Crimping dengan Metode Overall Equipment Effectiveness - Ciptadi Tatag Tur Raharja; Deri Teguh Santoso; Rizal Hanifi; Nanang Burhan (Universitas Muhammadiyah Semarang, 2021)
Wire harness is one of the main components in motorized vehicles that serves to transmit electric current and signals to motorized vehicles. The crimping machine is a tool used to connect or unite cables with terminals and is also the initial stage in the wire harness production process. Based on the above background, this research is focused on the flow of the wire harness and crimping machine production process to analysed the effectiveness of their performance using the OEE (Overall Effectiveness Equipment) method. The function of this OEE method is to measure engine effectiveness based on three main ratios, namely availability, performance efficiency, and rate of product quality. The OEE method is also inseparable from the six big losses because to be able to find out where the biggest losses are in a production process. The results of the analysis that have been carried out obtained an average value of 93% availability, 98.32% performance efficiency, and 99.77% rate of product quality. The OEE value was obtained at 91.23% and the largest loss was obtained in the setup and adjustment losses section, which was 4.76%. The cause is the factor of human negligence in carrying out machine maintenance and the machine factor because the service life has exceeded the limit which causes the machine to be easily damaged.